Farm-level Autonomous Adaptation of European Agricultural Supply to Climate Change - Leclère, David; Jayet, Pierre-Alain; de Noblet-Ducoudré, Nathalie (Ecological economics, 2013)
The impact of climate change on European agriculture is subject to a significant uncertainty, which reflects the intertwined nature of agriculture. This issue involves a large number of processes, ranging from field to global scales, which have not been fully integrated yet. In this study, we intend to help bridging this gap by quantifying the effect of farm-scale autonomous adaptations in response to changes in climate. To do so, we use a modelling framework coupling the STICS generic crop model to the AROPAj microeconomic model of European agricultural supply. This study provides a first estimate of the role of such adaptations, consistent at the European scale while detailed across European regions. Farm-scale autonomous adaptations significantly alter the impact of climate change over Europe, by widely alleviating negative impacts on crop yields and gross margins. They significantly increase European production levels. However, they also have an important and heterogeneous impact on irrigation water withdrawals, which exacerbate the differences in ambient atmospheric carbon dioxide concentrations among climate change scenarios. ► Farm-scale autonomous adaptation of agriculture has been weakly studied. ► We assess its role in the response of European agriculture to climate change. ► We rely on a modeling framework building upon an interdisciplinary approach. ► Such adaptation alleviates negative impacts on crop yields and gross margins. ► This benefit is at the cost of dramatic rise in irrigation needs.